Pengaruh Model Pembelajaran Kooperatif Tipe Gallery Walk terhadap Hasil Belajar Pada Pelajaran Ekonomi Kelas X di SMA Negeri 1 Perbaungan - Yuni Mariani Manik, Darwin Bangun (Universitas PGRI Madiun, 2019)
This study aims to determine the effect of cooperative learning gallery walk type on learning outcomes of class X1 students in SMA Negeri 1 Perbaungan as well as an overview of student learning outcomes after the application of the learning model. This study used a Pre-Experimental Research Design The one Pretest-posttest Design group with a population of all students in class X1 Perbaungan 1 High School, amounting to 30 students. Because the population is relatively small so that samples are taken as much as 100% of the population, the number of samples in this study are 30 students (One Experimental Class). Data collection is done by using questionnaires, tests, observations, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the walk gallery type cooperative learning model had a correlation of 0.782 in the medium category with a simple regression analysis equation Y = -12.507 +1.641X. The results of hypothesis testing with SPSS obtained tcount = 6.640 and ttable of 2.048 with a calculated value abel t table with a value of 6.640 ³2.048 with a significance value of 0.000 so H1 is accepted and H0 is rejected, this indicates that the influence of the gallery walk type cooperative learning model on results studying class X1 Negeri 1 Perbaungan students. The magnitude of the contribution of the influence of the learning model is 61.2 percent, while 38.8 percent is influenced by other factors that have not been studied in this study.